Role of K+ Channels in M2 Muscarinic Receptor-Mediated Inhibition of Noradrenaline Release From the Rat Stomach - Kumiko Nakamura; Shoshiro Okada; Naoko Yamaguchi; Takahiro Shimizu; Keiko Yokotani; Kunihiko Yokotani (Elsevier, 2004)
Previously we reported the cholinergic M2 muscarinic receptor-mediated inhibition of noradrenaline release from the rat stomach (K. Yokotani, Y. Osumi. J Pharmacol Exp Ther. 1993;264:54-60). In the present study, we investigated the role of K+ channels in oxotremorine (a muscarinic receptor agonist)-induced inhibition of noradrenaline release using isolated, vascularly perfused rat stomach. The gastric postganglionic sympathetic nerves were electrically stimulated twice at 2.5 Hz for 1 min and test reagents were added during the second stimulation. The electrically evoked release of noradrenaline was augmented by tetraethylammonium and 4-aminopyridine (non-selective K+ channel blockers) and also by charybdotoxin (a blocker of big conductance Ca2+-activated K+ channel). On the other hand, apamin (a selective blocker of small conductance Ca2+-activated K+ channels) and glibenclamide (an ATP-activated K+ channel blocker) had no effect on the evoked noradrenaline release. Oxotremorine-induced inhibition of noradrenaline release was attenuated by tetraethylammonium and 4-aminopyridine, while the inhibition was not influenced by charybdotoxin, apamin, and glibenclamide. These results suggest that tetraethylammonium- and 4-aminopyridine-sensitive K+ channels (probably voltage-activated K+ channels) are involved in the muscarinic receptor-mediated inhibition of noradrenaline release from the rat stomach. Keywords:: K+ channel, muscarinic inhibition, noradrenaline release, sympathetic nerve, rat stomach